mRNA vaccine with unmodified uridine induces robust type I interferon-dependent anti-tumor immunity in a melanoma model - Sittplangkoon, Chutamath; Alameh, Mohamad-Gabriel; Weissman, Drew; Lin, Paulo J. C.; Tam, Ying K.; Prompetchara, Eakachai; Palaga, Tanapat (Frontiers in Immunology, 2022)
An mRNA with unmodified nucleosides induces type I interferons (IFN-I) through the stimulation of innate immune sensors. Whether IFN-I induced by mRNA vaccine is crucial for anti-tumor immune response remains to be elucidated. In this study, we investigated the immunogenicity and anti-tumor responses of mRNA encoding tumor antigens with different degrees of N1-methylpseudouridine (m1Ψ) modification in B16 melanoma model. Our results demonstrated that ovalbumin (OVA) encoding mRNA formulated in a lipid nanoparticle (OVA-LNP) induced substantial IFN-I production and the maturation of dendritic cells (DCs) with negative correlation with increasing percentages of m1Ψ modification. In B16-OVA murine melanoma model, unmodified OVA-LNP significantly reduced tumor growth and prolonged survival, compared to OVA-LNP with m1Ψ modification. This robust anti-tumor effect correlated with the increase in intratumoral CD40+ DCs and the frequency of granzyme B+/IFN-γ+/TNF-α+ polyfunctional OVA peptide-specific CD8+ T cells. Blocking type I IFN receptor completely reversed the anti-tumor immunity of unmodified mRNA-OVA reflected in a significant decrease in OVA-specific IFN-γ secreting T cells and enrichment of PD-1+ tumor-infiltrating T cells. The robust anti-tumor effect of unmodified OVA-LNP was also observed in the lung metastatic tumor model. Finally, this mRNA vaccine was tested using B16 melanoma neoantigens (Pbk-Actn4) which resulted in delayed tumor growth. Taken together, our findings demonstrated that an unmodified mRNA vaccine induces IFN-I production or the downstream signaling cascades which plays a crucial role in inducing robust anti-tumor T cell response for controlling tumor growth and metastasis.